Handbook of research on entrepreneurship, innovation, sustainability, and ICTs in the post-COVID-19 era - Carvalho, Luísa Cagica 1970-; Reis, Leonilde 1962-; Silveira, Clara (2021)
ICT has had a huge impact on businesses and organizations in general, with new business models, new marketing channels, and new markets being reached using these technologies. ICT can promote new strategies and enhancers to optimize various aspects of business, but this technology also provides important tools that can empower social entrepreneurship initiatives to develop, fund, and implement new and innovative solutions to social, cultural, and environmental problems. With the upheaval caused by the COVID-19 pandemic and its subsequent impact on the economy, the methods and tools used within this field will be forever impacted. ICTs and the digital economy are huge trends that will affect organizations in several dimensions, such as how to communicate and improve performance. Thus, new perspectives and research are needed to identify the trends emerging in these fields.The Handbook of Research on Entrepreneurship, Innovation, Sustainability, and ICTs in the Post-COVID-19 Era broadens the exploitation of entrepreneurship, innovation, and ICTs in a global approach to draw attention to multidisciplinary perspectives of these contexts and their influence in modern organizations. In addition, the book explores and discusses, through innovative studies, case studies, systematic literature reviews, and reports, the key developments in digital entrepreneurship, circular economy and digitalization, digital business models, digital market and internationalization, digital economy, trends and challenges for organizations, digital entrepreneurial ecosystems, IS/ICT in organizations, social aspects of information systems, and more. This book is ideally intended for business managers, industry professionals, entrepreneurs, practitioners, stakeholders, researchers, academicians, and students looking for how business and organizations are going to shift and advance in the post-COVID-19 era